PEMBUATAN FILM â€œMENDAKI LANGITâ€ SEBAGAI MEDIA EDUKASI MASYARAKAT PEKALONGAN UNTUK MENINGKATKAN ANGKA LAMA SEKOLAH - Ulya, Inayatul; Matra, Sarlita D.; Haryanto, Muhamad (BAPPEDA Kota Pekalongan, 2016)
INCREASING NUMBER OF DROP OUT STUDENTS (SHOULD BE 9 YEARS) EACH YEAR HAS ELEVATED A SERIOUS PROBLEM IN DEGRADING THE QUALITY OF EDUCATION IN INDONESIA. THE PROBLEMS LAY ON THE PARENTING METHOD WHICH MIGHT NOT BE THE FOCUS OF THE GOVERNMENTâ€™S CONCERN. THE FACT THAT THE GOVERNMENT ONLY FOCUSES ON REVISING THE CURRICULUM AND GIVING THE SCHOLARSHIP HERE AND THERE CAUSE ANOTHER CONSIDERATION. THIS RESEARCH TRIED TO REVEAL THE PROBLEMS REALLY HAPPENED IN A REAL SOCIETY THAT LATER REFLECTS ON THE STORY OF A FILM ENTITLED â€œMENDAKI LANGITâ€. THIS RESEARCH USED RESEARCH AND DEVELOPMENT (R&D) RESEARCH DESIGN. MORE THAN 10 SCHOOLS WHICH HAVE THE MAJORITY NUMBER OF DROP OUT STUDENTS EMPLOYED IN THIS STUDY. BASED ON DEEP ANALYSIS ON THE PROBLEMS FACED BY THE STUDENTS THROUGH INTERVIEWS AND OBSERVATIONS, A FILM ABOUT FALSE PARENTING METHOD REFLECTED; SUCH AS THE LACK OF PARENTSâ€™ ATTENTION ON EDUCATION, THE IMPACT OF BROKEN HOME AND NEGATIVE PEERSâ€™ AND MEDIA INFLUENCES THAT MADE THE STUDENTS BECOME MISLEAD AND UNMOTIVATED IN SCHOOLS. FROM THIS FILM, THE PARENTS AS WELL AS THE SCHOOL MEMBERS SHOULD BE MORE RESPONSIBLE IN TAKING A GOOD CARE OF THE CHILDREN. THE GOVERNMENT SHOULD INCREASE THE SUPPORTS ON FUNDING